Prenatal maternal stress: triangulating evidence for intrauterine exposure effects on birth and early childhood outcomes across multiple approaches - Ingunn Olea Lund; Laurie J. Hannigan; Helga Ask; Adrian D. Askelund; Laura Hegemann; Elizabeth C. Corfield; Robyn E. Wootton; Yasmin I. Ahmadzadeh; George Davey Smith; Tom A. McAdams; Eivind Ystrom; Alexandra Havdahl (BMC Medicine)
Abstract Background Maternal stress during pregnancy may impact offspring development via changes in the intrauterine environment. However, genetic and environmental factors shared between mothers and children might skew our understanding of this pathway. This study assesses whether prenatal maternal stress has causal links to offspring outcomes: birthweight, gestational age, or emotional and behavioral difficulties, triangulating across methods that account for various measured and unmeasured confounders. Methods We used data from the Norwegian Mother, Father, and Child Cohort Study (MoBa), including maternal reports on prenatal stress at work, at home, and via stressful life events as exposures. Outcomes were children’s birthweight and gestational age, from the Medical Birth Registry of Norway, and maternal reports on early offspring emotional and behavioral difficulties. We assessed associations using four approaches: sibling control analyses, gene-environment interaction analyses, intergenerational Mendelian randomization (MR), and negative control (i.e., postnatal stress) analyses. Results Maternal prenatal stress was observationally associated with offspring lower birthweight (e.g., βwork = − 0.01 [95%CI: − 0.02, − 0.01]), earlier birth (e.g., βwork = − 0.04 [95%CI: − 0.04, − 0.03])), and more emotional (e.g., βevents = 0.08 [95%CI: 0.07, 0.09]) and behavioral difficulties (e.g., βrelationship = 0.08 [95%CI: 0.07, 0.09]) in the full sample (N = 112,784). However, sibling control analyses (N = 36,511) revealed substantial attenuation of all associations after accounting for familial factors. Gene-environment interaction models (N = 76,288) showed no clear evidence of moderation of associations by mothers’ polygenic scores for traits linked to stress sensitivity. Intergenerational MR analyses (N = 29,288) showed no clear evidence of causal effects of maternal plasma cortisol on any offspring outcomes. Negative control exposure analyses revealed similar effect sizes whether exposures were measured prenatally or postnatally. Conclusions Our results indicate that links between prenatal maternal stress and variation in early offspring outcomes are more likely to be confounded than causal. While no observational study can rule out causality, the consistency of our findings across different approaches is striking. Other sources of prenatal stress or more extreme levels may represent intrauterine causal risk factors for offspring development. Nonetheless, our research contributes to identifying boundary conditions of the fetal programming and developmental origins of health and disease hypotheses, which may not be as universal as sometimes assumed.